OTHR-13. IMPACT the brain: improving metastatic breast cancer patient access to coordinated treatment. (9th August 2021) - Grogan, Nicole; Pierce-Gjeldum, Donna; Swartz, Leigh; Verbal, Kait; Merajver, Sofia; Friese, Christopher; Kiyota, Ayano; Heth, Jason; Leung, Denise; Smith, Sean; Gabel, Nicolette; Kim, Michelle; et al.
Abstract: Central nervous system (CNS) metastases are associated with decreased survival and quality of life for patients with metastatic breast cancer (MBC). Multi-disciplinary care can optimize outcomes. This project aims to improve access to coordinated care for patients with MBC and CNS metastases. Patients with MBC and CNS metastases are referred and offered to enroll in our care coordination program. A team consisting of specialists (breast medical oncology, breast cancer genetics, radiation oncology, neurosurgery, neuro-oncology, physical medicine and rehabilitation (PM&R), neuropsychology, and palliative care) supports a dedicated program coordinator who provides navigation, education, specialty referral, and clinical trial screening. A unique intake form developed for the program creates personalized, coordinated, and expedited referrals. Patient-reported outcomes and caregiver burden assessments are collected. Since May 2020, 43 patients were referred and a total of 40 patients (93%) were enrolled – 2 (5%) declined due to perceived burden of participation and 1 (2%) died before enrollment. 85% of patients were Caucasian (n = 34) and 15% were non-Caucasian (n=6). Median time to program intake was 1 day (range: 0–8 days). Of the 43 patients referred, 17 (40%) consented to research studies in the metastatic setting. 11 were for an interventional trial (65%), while 9 consents were for non-interventional studies (53%). In addition to the initially referred specialty, 56 referrals were made across 7 sub-specialties; 37 patients (66%) were subsequently seen by a sub-specialist, most commonly radiation oncology (n = 9), neuro-oncology (n=8), PM&R (n=8), and neuropsychology (n=8). Implementation of a care coordination program for patients with MBC and CNS metastases is feasible. Further, it allows for improved access to care across sub-specialties and supports participation in clinical research for a group of cancer patients historically underrepresented in research studies. Funding : National Comprehensive Cancer Network Oncology Research Program from financial support provided by Pfizer.